Relationships among CO2 Emissions, Economic Growth and Foreign Direct Investment and the EKC Hypothesis in Turkey - BALIBEY, Mesut (International Journal of Energy Economics and Policy, 2015)
This study examines the causal relationships between economic growth, carbon dioxide emission and foreign direct investment and evaluates the Environmental Kuznets Curve (EKC) hypothesis for Turkey in 1974-2011. Firstly, the causality relationships investigated by using the Johansen Cointegration Test, The Granger Causality Test, Impulse-Response and Variance Decomposition Analysis of Vector Autoregression Model (VAR) model. The causality relationships display that foreign direct investment (LFDI) and economic growth (LGDP) have a significant effect on carbon dioxide emissions (LCO2). Moreover, impulse-response functions and variance-decompositions of VAR model support these relationships among LGDP, LCO2 and LFDI. Secondly, the study investigates the validity of the EKC hypothesis in Turkey for the period 1974-2011 by using Regression Model approach for the various EKC model forms such as linear, quadratic, and cubic. Consequently, economic growth leads to degradation of environment and depletion of natural resources. It must be the major aim to obtain a sustainable economic growth by less CO2 emissions and consuming less energy. Moreover, the policy makers may take account exogenous impacts such as foreign investments to plan energy policies, and to maintain economic growth against global climate warming. Keyword: EKC Hypothesis; CO2 Emission, Economic Growth; Granger Causality; Johansen Cointeration; Impulse-Response. JEL Classifications: C58; C51; Q43; Q56